Upaya Konservasi Cendrawasih Kecil (Paradisaea minor Shaw, 1809) YANG DILAKUKAN OLEH TAMAN BURUNG TMII DAN MBOF - Ken Dara Cita; Jarwadi Budi Hernowo; Burhanuddin Masyud (Media Konservasi, 2016)
Ex situ conservation is one of the ways to save wildlife animal include lesser bird of paradise. Taman Mini Indonesia Indah (TMII) Bird Park and Mega Bird And Orchid Farm (MBOF) were two institutions that support ex-situ conservation program with different purposes. TMII Bird Park has non-commercial purpose breeding, while MBOF has commercial purpose in captivity breeding. The objectives of this research were to describe the management of captive breeding of lesser bird of paradise with the influencing factor for captive breeding success and the daily behavior of lesser bird of paradise in the cage. This research was conducted from March until April 2015. Focal animal sampling and one zero sampling methods were employed to observe daily behavior. The results showed that in both locations there were two kind of cages for lesser bird of paradise display cage and quarantine cage. The temperature in the TMII Bird Park display cage was 25,51⁰C, meanwhile the temperature in the MBOF display cage was 22,68⁰C. There were not differences in management between the two locations, included management of cage, feed, care and health. Two institutions did not success for captive breeding lesser bird of paradise. The behavior had been identified were: resting, ingestive, and maintenance behavior.Keywords: daily behavior, lesser bird of paradise, management of captivity